Species range evolution of the rocky intertidal leaf oyster Isognomon nucleus (Lamarck, 1819) in the Indo-Pacific - Patteera Mahyotsanun; Adnan Shahdadi; Monthon Ganmanee; Benny K. K. Chan (Global Ecology and Conservation, 2026)
The small-sized leaf oyster, Isognomon nucleus , inhabits intertidal rock crevices across the tropical and subtropical Indo-Pacific (IP). This study examines the phylogeography of I. nucleus across the IP and the evolution of its distribution range using three mitochondrial markers, COX1 , 12S , and 16S , and the nuclear ITS1 marker. Our phylogenetic analyses revealed a widely distributed Indo-Pacific lineage of I. nucleus from the Andaman Sea to Hawaii, and two further deeply diverged but morphologically cryptic lineages: Isognomon cf . nucleus 1, restricted to Taiwan, and Isognomon cf . nucleus 2, occurring in Taiwan and Hainan (China). Phylogeographic analyses revealed extensive gene flow within I. nucleus , spanning from the Andaman Sea in the Indian Ocean through the Philippines and Taiwan in the western Pacific to Hawaii in the Central Pacific. This high dispersal capacity is likely facilitated by west–east flowing equatorial currents and the species’ strong environmental tolerance. Higher pairwise Φst values between Hawaii and other localities indicate reduced gene flow between Hawaii and the Indo–West Pacific, consistent with Hawaii’s geographic isolation. The Hawaiian endemic Isognomon californicus is closely related to I. cf . nucleus 1, suggesting that both evolved from a common ancestor and diverged as a result of limited dispersal between Taiwan and Hawaii. Demographic analyses detected clear signals of population expansion in I. nucleus coinciding with the sea level changes in the Last Glacial Maximum.
Keywords: Marine Bivalve and Aquaculture Studies; Marine Ecology and Invasive Species; Crustacean biology and ecology